The Effectiveness of Group Counseling Using The Approach Cognitive Behavioral Therapy (CBT) With Improved Cognitive Restructuring Techniques Self-Confidence of Pre-Prosperous Students - Putra, Tomi; Firman, Firman (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Poverty in Indonesia continues to increase from year to year, including in West Sumatra Province. The government is trying to overcome this problem through the Smart Indonesia Program (PIP) in the form of scholarships, to help students from underprivileged families obtain a decent education. However, many scholarship recipients still experience low self-confidence. This study aims to analyze the effectiveness of group counseling using the Cognitive Behavioral Therapy (CBT) cognitive restructuring techniques in increasing the self-confidence of underprivileged students at SMKN 5 Padang. This study uses a quantitative method with a quasi-experimental design in the form ofpretest-posttest control group design. The sample consisted of 16 students who were divided into experimental and control groups, each consisting of 8 people, through the technique cluster random sampling. The instrument uses a Likert scale, and the data is analyzed using Wilcoxon Signed Ranks Test and Mann Whitney Test. The results of the study showed that the CBT approach with cognitive restructuring techniques was significantly effective in increasing the self-confidence of underprivileged students. This study recommends CBT-based group counseling services as an intervention strategy for BK teachers in schools.